Positive Consequences of False Memories. (11th July 2013) - Howe, Mark L.; Garner, Sarah R.; Patel, Megan; Otgaar, Henry; Sauerland, Melanie; Petrila, John P.
<x xml:space="preserve">Abstract</x> Previous research is replete with examples of the negative consequences of false memories. In the current research, we provide a different perspective on false memories and their development and demonstrate that false memories can have positive consequences. Specifically, we examined the role false memories play in subsequent problem‐solving tasks. Children and adults studied and recalled neutral or survival‐relevant lists of associated words. They then solved age‐normed compound remote associates, some of whose solutions had been primed by false memories created when studying the previous lists. The results showed that regardless of age: (a) survival‐related words were not only better recollected but were also more susceptible than neutral words to false memory illusions; and (b) survival‐related false memories were better than neutral false memories as primes for problem‐solving. These findings are discussed in the context of recent speculation concerning the positive consequences of false memories, and the adaptive nature of reconstructive memory. Copyright © 2013 John Wiley & Sons, Ltd.